2015 10th International Workshop on the Electromagnetic Compatibility of Integrated Circuits (EMC Compo) 2015
DOI: 10.1109/emccompo.2015.7358367
|View full text |Cite
|
Sign up to set email alerts
|

Developing a universal exchange format for Integrated Circuit Emission Model - Conducted Emissions

Abstract: A new international standard proposal (IEC 62433-2 Edition 2.0) is in progress. The main purpose of the standard is to provide an Integrated Circuit Emission Model -Conducted Emission (ICEM-CE) along with a data exchange format. It is known that the existing ICEM-CE information is closely linked to the supplier of the model or simulation software used to generate the model information, rendering extremely difficult its exchange between suppliers, customers, EDA tool vendors, academics, etc. This paper describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…As for these matters, various research has been reported in the past years [11][12][13]. Reference [14] gives an overview of the EMC research focusing on chip-level.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As for these matters, various research has been reported in the past years [11][12][13]. Reference [14] gives an overview of the EMC research focusing on chip-level.…”
Section: Introductionmentioning
confidence: 99%
“…Hyun Ho Park, et al generated a macro model of the timing controller chip for running pseudo H pattern data from transistor level simulation and is used to estimate the power switching current on the printed circuit board (PCB) [23]. Abhishek Ramanujan, et al designed a common interchange format for ICEM based on the well-known extensible markup language format and applied to Atmega88 microcontrollers [13]. Modeling methods for PCB and components with both chips and packages were published in [24] and [25], in order to calculate PCB power noise generated by the switching chip.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation